2022
DOI: 10.3390/nano12050740
|View full text |Cite
|
Sign up to set email alerts
|

Wettability Improvement in Oil–Water Separation by Nano-Pillar ZnO Texturing

Abstract: The nanostructure-based surface texturing can be used to improve the materials wettability. Regarding oil–water separation, designing a surface with special wettability is as an important approach to improve the separation efficiency. Herein, a ZnO nanostructure was prepared by a two-step process for sol–gel process and crystal growth from the liquid phase to achieve both a superhydrophobicity in oil and a superoleophobic property in water. It is found that the filter material with nanostructures presented an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Adhesion is the result of molecular or atomic forces between objects, causing them to bond closely [79]. This phenomenon involves various mechanisms of adhesion, among which van der Waals forces generate short-range attractions between molecules, including London dispersion forces and Debye polarization forces, creating temporary charge distributions and resulting in attraction [48,80,81].…”
Section: Mechanism and Failure Modementioning
confidence: 99%
“…Adhesion is the result of molecular or atomic forces between objects, causing them to bond closely [79]. This phenomenon involves various mechanisms of adhesion, among which van der Waals forces generate short-range attractions between molecules, including London dispersion forces and Debye polarization forces, creating temporary charge distributions and resulting in attraction [48,80,81].…”
Section: Mechanism and Failure Modementioning
confidence: 99%
“…Designing a surface with special wettability is an important approach to improving the separation efficiency of oil and water. Liu and co-authors demonstrated superhydrophobicity in both oil and water from their stainless-steel metal fibers coated with sol–gel-derived ZnO nano-pillars [ 8 ]. They found that their ZnO-coated stainless-steel metal fibers had a static underwater oil contact angle of 151.4° ± 0.8° and an underoil water contact angle of 152.7° ± 0.6° and was a highly promising candidate for both water-in-oil and oil-in-water separation in the industry.…”
mentioning
confidence: 99%